2008
DOI: 10.1210/jc.2008-0660
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Economic Outcomes of Thyroid and Parathyroid Surgery in Children

Abstract: Children undergoing thyroidectomy/parathyroidectomy have higher complication rates than adult patients. Outcomes were optimized when surgeries were performed by high-volume surgeons. There appears to be disparity in access to high-volume surgeons for children from low-income families, Blacks, and Hispanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
210
2
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(231 citation statements)
references
References 25 publications
9
210
2
10
Order By: Relevance
“…In the largest study of pediatric DTCs, Demidchik found a complication rate of 22%, including permanent recurrent nerve damage in 6.2% and permanent hypoparathyroidism in 12.3% [39]. Children have higher endocrine-specific complication rates than adults after thyroidectomy (9.1 vs. 6.3%) [43].…”
Section: Treatment -Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…In the largest study of pediatric DTCs, Demidchik found a complication rate of 22%, including permanent recurrent nerve damage in 6.2% and permanent hypoparathyroidism in 12.3% [39]. Children have higher endocrine-specific complication rates than adults after thyroidectomy (9.1 vs. 6.3%) [43].…”
Section: Treatment -Surgerymentioning
confidence: 99%
“…Hence it is recommended that these surgeries be performed by high-volume thyroid surgeons (defined as performing more than 30 thyroid surgeries per year) to minimise complications [6,7,43], which may still occur in about 6% of cases [43].…”
Section: Treatment -Surgerymentioning
confidence: 99%
“…Complications, such as hypoparathyroidism, vocal cord palsy due to recurrent laryngeal nerve injury and keloid formation, may occur with an estimated incidence of approximately 15%, although such complications are less frequent if the operation is performed by pediatric surgeons with extensive experience (18). For patients with recurrent hyperthyroidism after surgery, treatment with RAI is recommended, because the risk of complications is higher for a second operation (19).…”
Section: Introductionmentioning
confidence: 99%
“…Debido al mayor riesgo de malignidad en los NTP, suele preferirse el tratamiento quirúrgico como primera aproximación a esta patología, considerando de manera limitada el aporte de la PAF, en gran parte debido a la falta de consenso sobre el uso de esta técnica en pediatría. Sin embargo, el tratamiento quirúr- gico en esta edad presenta una mayor incidencia de complicaciones que en adultos, especialmente a menor edad del paciente 14 . Las complicaciones incluyen la injuria del nervio laríngeo recurrente (0 a 40%) e hipoparatiroidismo permanente (0 a 32%), las que disminuyen si el procedimiento es realizado por un cirujano de alto volumen, definido como aquel que realiza más de 30 cirugías tiroideas al año 14 .…”
unclassified
“…Sin embargo, el tratamiento quirúr- gico en esta edad presenta una mayor incidencia de complicaciones que en adultos, especialmente a menor edad del paciente 14 . Las complicaciones incluyen la injuria del nervio laríngeo recurrente (0 a 40%) e hipoparatiroidismo permanente (0 a 32%), las que disminuyen si el procedimiento es realizado por un cirujano de alto volumen, definido como aquel que realiza más de 30 cirugías tiroideas al año 14 . Para que la citología tiroidea por PAF sea adecuada en la población pediátrica, es necesaria la cooperación del paciente para que la punción sea precisa, por esta razón frecuentemente se realiza bajo sedación.…”
unclassified